The effect of low level diode laser in treatment of recurrent apthous stomatitis (case study) - Dalia saleem kareem; Layla M. H. Al-ameri; Ammar Saleh Alalawi (Iraqi Journal of Laser, 2025)
Objective: Recurrent Aphthous Stomatitis (RAS) is a common, painful, and recurrent oral condition characterized by ulcer formation. Its pathogenesis is multifactorial, involving genetic, immunological, and environmental factors. conventional methods like topical anesthetics, such as benzocaine. Mouth rinses containing hydrogen peroxide, chlorhexidine, or dexamethasone. Corticosteroid ointments, such as fluocinonide, beclomethasone, or hydrocortisone hemosuccinate, primarily focus on symptom relief rather than cure. Low-level laser therapy (LLLT) has emerged as a promising treatment modality, offering minimal invasiveness and effective healing. Case Presentation:  A 28-year-old female patient presented with a painful ulceration (6*5mm) with edematous border on the lateral surface of her tongue,  after clinical examination (ulcer duration and frequency, the number of ulcers present, their shape and size, location, and specific characteristics such as the edges, base, and the condition of the surrounding tissues). and the medical history of the patient diagnosed as Recurrent Aphthous Stomatitis.  The condition is treated by using low-level diode laser therapy. using a diode laser 980 nm with the power set at 1W, a non-contact laser application. The distance between the laser probe’s tip and the ulcer surface was meticulously maintained at 10mm. A single laser treatment session consisted of four 30-second applications, separated by a 15-second interval. The cumulative laser application time amounted to approximately 120 seconds.Conclusion: Low-level diode laser therapy significantly reduces pain, lesion size, and edema in RAS patients, while improving patient satisfaction, functional ability, and reducing Interleukin-1 beta (IL1β), Transforming Growth Factor-beta 1 ( TGFβ-1) serum levels.